If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+6=7x-26
We simplify the equation to the form, which is simple to understand
3x+6=7x-26
We move all terms containing x to the left and all other terms to the right.
+3x-7x=-26-6
We simplify left and right side of the equation.
-4x=-32
We divide both sides of the equation by -4 to get x.
x=8
| x*.75+(100-X)(.5)=(x+100)(.6) | | 5/4+1=x | | 5x+1=9x-15 | | -7x^2+44x-12=0 | | N=n+2 | | w^2+3=39 | | 122-6x=12x+18 | | 2/(6x^2+3x-1) | | 3x-2(3x-2)=4-x+3 | | 4x+11=7x-7 | | 10w-22=38 | | 4(x-2)=4x+10 | | 28+2x(x+3)+6(x-3)=0 | | 2/6x^2+3x-1 | | 13(-45a+27)=(13-8a-10) | | 4x+5[3+x]=87 | | 4p=240 | | 4+2w=19-w | | 4y^2=-17y-4 | | 91/2-82/5 | | 3x+1=-872 | | 7x-12=-36+4x | | a*a+ab+a= | | 5x-2x=2x-2 | | 5a+3/4b | | 3x-4y=8fory | | w(w+.11)=.057 | | 4a+1/4b | | x^4+18.19x^2-225=0 | | d=h | | 4a+1/B | | 8+8=91 |